Konsep Pembaharuan Muhammad Bin Abdul Wahab - Syamsuez Salihima (Rihlah : Jurnal Sejarah dan Kebudayaan, 2013)
Wahabi is a religious movement organization established by Muhammad Ibn-‘Abd Al-Wahhab (1703-1791). The term of Wahabi is attributed to his name. The main teaching of this organization is tauhid constitutes the nucleus doctrine of Islamic teaching. The unity of God is revealed in the three forms; firstly, Tauhid  al-Rububiyah, explaining the unity of God and his action. God is creator, preserver, and decider of this universe. Secondly: Tauhid al-Asma’ wa al-Sifat (the unity of name and attributes) which is related to God’s attributes. He is the owner of anything in this universe, and thirdly, Tauhid al-Ilahiyah; explaining that He is the only God absolutely worshipped. There is no God but Him and Muhammad is His messenger. It means that all worships is just for Him. Muhammad is not worshipped but he is obeyed and followed.